Artificial Intelligence Leadership and Employee Engagement in Contemporary Organizations: A Literature Review - Willy Chandra; Ruslaini Ruslaini; Tanti Sugiharti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the factors influencing employee engagement in AI-driven organizations, particularly from the perspective of Artificial Intelligence (AI) leadership. This literature review focuses on the relationship between AI leadership, AI utilization, and employee engagement in contemporary organizational settings. The review was based on recent empirical studies selected according to their relevance to artificial intelligence, leadership, employee engagement, work engagement, and knowledge sharing. The analysis indicates that AI does not inherently improve employee engagement merely through its availability in the workplace. Employee engagement is likely to improve with AI-savvy leadership that is supported by meaningful AI utilization, an innovative organizational culture, effective change leadership, work engagement, and enhanced team performance. AI implementation can promote employee knowledge sharing through learning opportunities, especially when supported by paradoxical leadership and positive employee attitudes toward technology. Therefore, this review highlights the importance of human-centered leadership in enabling employees to experience AI as a source of learning, collaboration, empowerment, and meaningful contribution.